Comparative Life Cycle Assessment of ceramic versus concrete roof tiles in the Brazilian context. (15th February 2015) - Souza, Danielle Maia de; Lafontaine, Mia; Charron-Doucet, François; Bengoa, Xavier; Chappert, Benoit; Duarte, Fernanda; Lima, Luis
Abstract: The Brazilian ceramic industry is responsible for providing more than 90% of the roof coverings and wall bricks in the country, producing more than 15 billion pieces per year. In order to compare the life cycle impacts of ceramic versus concrete roofing tiles and identify potential improvements in ceramic products, we carried out a life cycle impact assessment of both products. This study aimed to compare the life cycle impacts of ceramic and concrete roof coverage over 1 m 2, with an assumed life time of 20 years in Brazil. Nine different sensitivity analyses were carried out followed by a Monte Carlo uncertainty analysis to verify the robustness of the study. The results show that ceramic tiles appear to have less impact than concrete tiles on Climate Change, Resource Depletion and Water Withdrawal, while for the remaining damage categories, Human Health and Ecosystem Quality, the difference between the two alternatives was too low to be considered significant. The use of wood chips led to significant impacts, mainly related to respiratory inorganics. Assessment of the data quality identified that the data is of generally high or acceptable quality. The sensitivity analysis and uncertainty assessment show that the conclusions are robust. Graphical abstract: Highlights: We modeled the life cycle environmental impacts of two different options for roof tiles in Brazil. The concrete manufacturing process has a great impact on Climate Change and Resource Depletion. Higher impact on Water Withdrawal is linked to concrete tiles. Uncertainty in Human Health and Ecosystem Quality modeling was higher than difference in results.